Short Communication: Potential tests of plant growth bacteria for the control of Peronosclerospora philipinensis in corn - Nurasiah Djaenuddin; SYAFRUDDIN SYAFRUDDIN; BAHARUDDIN PATANDJENGI; TUTIK KUSWINANTI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Djaenuddin N, Syafruddin, Patandjengi B, Kuswinanti T. 2020. Short Communication: Potential tests of plant growth bacteria for the control of Peronosclerospora philipinensis in corn. Biodiversitas 21: 3886-3892. The study was conducted at the Laboratory and Screen House of the Indonesian Cereals Research Institute (ICERI). The stages of the study were (i) potential test of bacterial isolates that have the ability to control downy mildew disease in vivo in corn and (ii) molecular identification of the selected bacterial isolates. Experiments were arranged in a Completely Randomized Design (CRD) with treatment of 24 bacteria which suspected to be growth-promoting bacteria. The parameters observed were disease intensity, percent disease suppression, plant height, chlorophyll content, and crop wet weight. The result showed that only five bacterial isolates namely, Bacillus albus strain MCCC 1A02146, Bacillus cereus strain IAM 12605, Bacillus paramycoides strain MCCC 1A04098, Pseudomonas stutzeri strain CCUG 11256, Serratia marcescens subsp. sakuensis strain KRED, have the ability to induce resistance to downy mildew disease caused by Peronosclerospora philipinensis.